Dynamic reform of public institutions: A model of motivated agents and collective reputation - Justin Valasek (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2016)
State capacity is optimized when public institutions are staffed by individuals with public-service motivation. However, when motivated agents value the collective reputation of their place of employment, steady-state equilibria with both high and low aggregate motivation (reputation) in the mission-oriented sector exist. Reforming a low-motivation institution requires a non-monotonic wage path: since the effect of higher wages on motivation is negative for a highreputation institution, but positive for a low-reputation institution, a transition to a high-reputation steady state requires an initial wage increase to crowd motivated workers in, followed by a wage decrease to crowd non-motivated workers out.
Keywords: D23; D73; L32; 330; Motivated Agents; Institutional Reform; Public Sector